Living with floods : an exercise in alternatives - Ahmed, Imtiaz, 1958- (Dhaka : University Press, 1999)
In the context of Bangladesh, contributed articles.
Includes bibliographical references and index.
Keywords: Floods -- Bangladesh -- Dhaka; Disaster relief -- Bangladesh -- Dhaka